“And I Can Remind Myself That I Am All Of This”: adolescents’ experiences of group-based acceptance and commitment therapy - Brovold, Filippa; Laugen, Nina Jakhelln; Grøtte, Torun (Frontiers in Psychology, 2024)
Introduction: A growing body of literature supports the use of Acceptance-and commitment therapy (ACT) for a wide range of mental health problems in children and adolescents, but less is known about ACT when given to adolescents in a group format. Consequently, this study aimed to explore the subjective experiences of adolescents who had completed a group-based ACT for symptoms of anxiety and depression. Adolescents' perceptions of the core therapeutic processes of ACT and the means used to enhance them, as well as the interplay between ACT processes and the group format, were of primary interest. Method: Semi-structured qualitative interviews were conducted with seven adolescents, of which five were girls and two were boys, between 16 and 19 years old. Transcripts were analyzed using reflexive thematic analysis. Results: The adolescents varied greatly in their experience of ACT's core processes and the methods used to enhance them. Most found the core processes meaningful and educational, especially appreciating the concept of values and value-based action. However, some perceived the core processes as irrelevant and provocative, particularly interpreting acceptance as "giving up." The metaphors and practical exercises were experiences as playful and instructive supplements to the more theoretical elements of therapy, but also as childish and embarrassing. The group format facilitated normalization and support and seemed to increase the adolescents' motivation and adherence to therapeutical work, but it also triggered socially anxious thoughts and self-censoring for some.The results from the current study support previous literature indicating that group-based ACT is an acceptable and feasible treatment format for adolescents. Yet, the varying experiences underscores the need for further studies exploring how to accommodate the group format to the diverse personal and developmental disparities in this age group. Randomized controlled trials are also needed to compare the effectiveness of individual versus group format of ACT for adolescents.